Logical Aspects Regarding the Conception of Intelligent Systems - Vasile Mazilescu (Risk in Contemporary Economy, 2016)
The present paper presents some logical aspects of symbolic AI Systems, applied to the Intelligent Systems design. The basic feature of these systems is represented by the processing of the imprecise and dynamic knowledge involved in the synthesis of some decisions. We consider that the paper tackles an up-to-date and little debated aspect especially in the field of decision fuzzy systems. Knowledge-based systems with real-time functioning bear features that the majority of classic systems do not have: reasoning is evolutionary and non-monotonous due to the dynamic nature of the application, and events can change the status of the expert management system. The management architectures based on symbolic techniques acquire characteristics specific to the domain problem and to the type of intelligent system based on a management knowledge structure.